Morphological evolution of the carnivoran sacrum. Issue 6 (12th July 2020) - Esteban, Juan Miguel; Martín‐Serra, Alberto; Varón‐González, Ceferino; Pérez‐Ramos, Alejandro; Velasco, David; Pastor, Francisco J.; Figueirido, Borja
Abstract: The sacrum is a key piece of the vertebrate skeleton, since it connects the caudal region with the presacral region of the vertebral column and the hind limbs through the pelvis. Therefore, understanding its form and function is of great relevance in vertebrate ecomorphology. However, it is striking that morphometric studies that quantify its morphological evolution in relation to function are scarce. The main goal of this study is to investigate the morphological evolution of the sacrum in relation to its function in the mammalian order Carnivora, using three‐dimensional (3D) geometric morphometrics. Principal component analysis under a phylogenetic background indicated that changes in sacrum morphology are mainly focused on the joint areas where it articulates with other parts of the skeleton allowing resistance to stress at these joints caused by increasing muscle loadings. In addition, we demonstrated that sacrum morphology is related to both the length of the tail relativised to the length of the body, and the length of the body relativised to body mass. We conclude that the sacrum in carnivores has evolved in response to the locomotor requirements of the species analysed, but in locomotion, each family has followed alternative morphological solutions to address the same functional demands. Abstract : The sacrum in carnivores has evolved in response to the locomotor requirements of the species analysed, but in locomotion, each family has followed alternative morphological solutions to address the same functional demands.